Quetiapine monotherapy versus placebo in the treatment of children and adolescents with bipolar depression: A systematic review and meta-analysis - Maneeton B. (2017)
© 2017 Maneeton et al. Background: Some studies have indicated the efficacy of quetiapine in the treatment of bipolar depression in adult patients. However, its efficacy has been not shown in child and adolescent patients. Objective: This systematic review purposefully determined the efficacy and acceptability of quetiapine in the treatment of children and adolescents with bipolar depression. Data sources: A database search of EMBASE, PubMed, CINAHL, and Cochrane Controlled Trials Register was carried out in March 2016. All randomized controlled trials (RCTs) of bipolar depression in children and adolescents were considered for inclusion in this review. Study eligibility criteria, participants, and interventions: RCTs of quetiapine in the treatment of child and adolescent patients with bipolar depression with end point outcomes were included in this study. Languages were not limited. Study appraisal and synthesis methods: The full-text versions of relevant clinical studies were thoroughly examined and extracted. The primary efficacy of outcome was measured by using the pooled mean-changed scores of the rating scales for bipolar depression. However, the response and remission rates were also measured. Results: A total of 251 randomized patients in the three RCTs of quetiapine versus placebo in the treatment of bipolar depression for children and adolescents were eligible in this review. The pooled mean-changed score of the quetiapine-treated group was not greater than that of the placebo-treated group. Similarly, the pooled response and remission rates were not different between the two groups. The pooled overall discontinuation rate and the discontinuation rate due to adverse events were not different between the two groups. Limitations: Limited studies were eligible in this review. Conclusion: According to the findings in this review, quetiapine may not be efficacious in the treatm ent of bipolar depression in children and adolescents. Its acceptability, however, was comparable to a placebo. Therefore, the use of quetiapine in children and adolescents with bipolar depression is not recommended. Further well-defined clinical studies should be performed to confirm these outcomes.